In the shadow of the ark - PROVOOST, ANNE (Arthur A. Levine Books, 2004)
In the Shadow of the Ark by Anne Provoost is a YA/adult crossover historical novel offering a haunting retelling of Noah's flood through the eyes of Re Jana, a skeptical young woman living in the worker camp around the ark.
English